Composite scaffolds for controlled drug release: Role of the polyurethane nanoparticles on the physical properties and cell behaviour. (April 2015) - Gentile, Piergiorgio; Bellucci, Devis; Sola, Antonella; Mattu, Clara; Cannillo, Valeria; Ciardelli, Gianluca
Abstract: Localised delivery of appropriate biomolecule/drug(s) can be suitable to prevent postoperative infections and inflammation after scaffold implantation in vivo . In this study composite shell scaffolds, based on an internally produced bioactive glass and a commercial hydroxyapatite, were surface coated with a uniform polymeric layer, embedded with thermo-stable polyesterurethane (PU)-based nanoparticles (NPs), containing an anti-inflammatory drug (indomethacin; IDCM). The obtained functionalised scaffolds were subjected to physico-mechanical and biological characterisations. The results indicated that NPs incorporation into the gelatin coating of the composite scaffolds: 1) not changed significantly the micro-architecture of the scaffolds in terms of mean pore diameter and pore size distribution; 2) increased the compressive modulus; and 3) allowed to a sustained IDMC release (65–70% of the loaded-drug) within the first week of incubation in physiological solution. On the other hand, the NPs incorporation did not affect the biocompatibility of composite scaffolds, as evidenced by viability and alkaline phosphatase (ALP) activity of MG63 human osteoblast-like cells.